2016
DOI: 10.5152/dir.2016.15232
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MDCT protocols in trauma patients with suspected splenic injury: superior results with protocol that includes arterial and portal venous phase imaging

Abstract: M agnetic resonance imaging (MRI) is a widely used diagnostic tool for breast imaging in daily practice, with its high sensitivity to detect primary, recurrent, and residual breast cancer. Breast MRI serves as a reliable problem-solving tool in case of inconclusive mammography and ultrasonography (US) findings. It can be used to monitor the results of neoadjuvant chemotherapy and it may also contribute to preoperative evaluation of known lesions. With increasing use of MRI, number of breast lesions visible onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…It should be noted that although we do not routinely perform an arterial phase CT scan of the abdomen and pelvis in patients with isolated blunt abdominal trauma, it has been shown that the combination of an arterial phase scan and a portal venous phase scan increases the sensitivity and accuracy for the detection of splenic vascular injury (24)(25)(26). However, in patients undergoing CT of the chest, abdomen, and pelvis because of high-velocity mechanisms of blunt trauma (namely, motor vehicle collisions), the arterial phase of the chest CT scan is extended inferiorly to include the splenic vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that although we do not routinely perform an arterial phase CT scan of the abdomen and pelvis in patients with isolated blunt abdominal trauma, it has been shown that the combination of an arterial phase scan and a portal venous phase scan increases the sensitivity and accuracy for the detection of splenic vascular injury (24)(25)(26). However, in patients undergoing CT of the chest, abdomen, and pelvis because of high-velocity mechanisms of blunt trauma (namely, motor vehicle collisions), the arterial phase of the chest CT scan is extended inferiorly to include the splenic vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…These two patients had a grade-4 splenic injury. Although the sensitivity and specificity of the computed tomography reach 80% in spleen injuries, it should be kept in mind that there may be injuries that imaging methods can miss in blunt abdominal trauma (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the widespread use of CT to evaluate the posttrauma patient whose condition is stable, the optimal CT trauma protocol remains an area of continued evaluation (24)(25)(26)(27)(28)(29), and there are few data on the ideal imaging protocol for trauma patients after DCS. The imaging should cover the thoracic inlet to the femoral trochanters in at least the portal venous phase, which is best suited for the detection and characterization of solid organ injuries, particularly hepatic or splenic parenchymal disruption (17,24).…”
Section: Ct Protocolsmentioning
confidence: 99%
“…Imaging in the brain and neck can be added when it is warranted clinically. The addition of arterial phase imaging improves the diagnostic yield for the identification and characterization of vascular injuries, both in isolation and within solid organs, particularly in the spleen (24)(25)(26)(27).…”
Section: Ct Protocolsmentioning
confidence: 99%